ON THE ISSUE OF EXTENSION OF JURISDICTION OF THE COURT WITH THE PARTICIPATION OF JURORS - Akhmejanov Фарух Раушанұлы; Birzhanova Дина Мухтаркызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2017)
The article contains the analysis of the legislation of the Republic of Kazakhstan, regulating the participation of jurors in consideration of criminal cases, as well as law enforcement practice in this field. The authors identified current trends related to changes in the jurisdiction of the court with the participation of jurors. In Kazakhstan the institution of the trial by jury was established with the adoption of the Law of the Republic of Kazakhstan “On Jurors” dated January 16, 2006, No. 121. As was argued by N. Shaykenov, it is impossible to build an efficient economy without the elevation of law and the court. In this regard, after the Republic of Kazakhstan declared its independence, certain reforms in the legislation were designated. There have been adopted dozens of new laws, in varying degrees aimed at improving the administration of justice. At the present time it can be stated that the level of applicability of this institution is relatively low. This fact is associated with the existing problematic issues both in terms of the objectivity of the jurors themselves, and in terms of limiting the possibility of taking an impartial decision by jurors under conditions of lack of procedural independence. Concerning the need to expand the sphere of application of the jury trial in Kazakhstan pursuant to step 21 of the Nation Plan – 100 concrete steps, it is proposed to base on clear juridical criteria in determining the category of cases to be considered by jury trials. The article suggests that the frequent changes in the list of constituent elements of crime are not conducive to the stable development of the institution of trial by jury as a whole. On the basis of conducted analysis there were identified some legislative provisions that require alterations and additions. In particular this concerns certain provisions of the Criminal Procedure Code of the Republic of Kazakhstan dated July 4, 2014, as well as the previously mentioned Law “On Jurors”. In addition, the authors raise questions about the conceptual review of the model of the court procedure with the participation of jurors. In this sense, it is necessary to study the existing classical model of jury trial in foreign countries.